Cryptococcus gattii genotype VGIIa infection imported from Vancouver Island to Japan. Issue 7 (July 2018) - Kitaura, Tsuyoshi; Takahashi, Masamichi; Umeyama, Takashi; Takeshita, Nozomi; Katanami, Yuichi; Takaya, Saho; Yamamoto, Kei; Kutsuna, Satoshi; Hayakawa, Kayoko; Kato, Yasuyuki; Yamauchi, Takahiro; Narita, Yoshitaka; et al.
Abstract: A 71-year-old Japanese man with travel history to the Vancouver Island, Canada was diagnosed the pulmonary and central nervous system infections caused by Cryptococcus gattii genotype VGIIa. This is the first imported case of Cryptococcus gattii genotype VGIIa infection from endemic area of North America to Japan. He was recovery with no residual neurological dysfunction by early resection of brain mass and antifungal therapy. Early surgical resection of cerebellar cryptococcoma may shorten the length of induction therapy with antifungal drugs.